Editorial: New frontiers in e-Business and e-Government - Feng Li; Savvas Papagiannidis; Alexis Barlow; Peter Duncan (International Journal of Business Science & Applied Management (IJBSAM), 2007)
This special issue will explore a wide range of issues, from the emerging opportunities and challenges of MMORPGs, the new media industries, emerging technologies and applications and new Challenges in e-Government and e-Public services, to using e-Business to facilitate regional economic developments.
Keywords: 650; e-business; e-government; e-public services; new technologies